2003
DOI: 10.1530/rep.0.1260171
|View full text |Cite
|
Sign up to set email alerts
|

Global gene profiling analysis of mouse uterus during the oestrous cycle

et al.

Abstract: Many genes related to the cyclic changes of the uterus during the oestrous cycle have been identified using a oneby-one approach. In the present study, cDNA microarray technology was applied to investigate the global profile of gene expression of mouse uterus at the oestrous and dioestrous stages. At a certain stage of the oestrous cycle, the uteri of mature CD-1 mice (n = 10) were removed, pooled and snap-frozen in liquid nitrogen. Total RNA was extracted to synthesize cDNA probes for microarray assay. By scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 34 publications
(4 reference statements)
2
23
0
Order By: Relevance
“…The serine protease cluster includes kallikrein 1 and several related peptidases, all of which were downregulated in estrus relative to proestrus (Supplemental Table S20B). Kallikrein 1 is downregulated in estrus relative to diestrus [6] and is increased by estrogen treatment [31]. Consistent with this, kallikrein 1 was upregulated in proestrus, i.e., when estrogen levels are high.…”
Section: Genes Affecting Uterine Morphology Architecture and Tissuesupporting
confidence: 65%
See 2 more Smart Citations
“…The serine protease cluster includes kallikrein 1 and several related peptidases, all of which were downregulated in estrus relative to proestrus (Supplemental Table S20B). Kallikrein 1 is downregulated in estrus relative to diestrus [6] and is increased by estrogen treatment [31]. Consistent with this, kallikrein 1 was upregulated in proestrus, i.e., when estrogen levels are high.…”
Section: Genes Affecting Uterine Morphology Architecture and Tissuesupporting
confidence: 65%
“…In addition, the expression of metalloproteinases (MMPs) increases toward the late-secretory phase [4] and decreases in the late proliferative phase [5]. The proliferative phase affects cellular proliferation and differentiation, extracellular matrix remodeling, angiogenesis, and vasculogenesis [5,6]. Genes related to adhesion and ion channels are also highly expressed at this phase [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrium [21,22], placenta, and liver [23] were included as positive controls for the detection of HSD17B2. Immunohistochemistry with the three anti-HSD17B2 antibodies on mouse endometrial tissues showed a strong positive signal specifically on epithelial cells, as expected (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Highly prominent genes in this category were the cell proliferation regulator, RXRA, whose expression was expected in atrophic glands (43,44), a tissue remodeling gene ADAMST1 and an estrogen-modulated gene, DMBT1, essential for epithelial proliferation and regeneration (45,46). The annotation of these highly expressed genes in Post-M endometrium suggests their possible functional role in regulating endometrial epithelial cell proliferation in the basalis of Pre-M and their potential roles in regulating putative resident ESP cells.…”
Section: Discussionmentioning
confidence: 99%